Digital Marketing Implementation For Product Recognition And Sales At PT Marsudi Utomo: Implementasi Pemasaran Digital Untuk Pengenalan Produk Dan Penjualan PT Marsudi Utomo - Rama Chikal Abimanyu; Mochamad Rizal Yulianto (Universitas Muhammadiyah Sidoarjo, 2026)
General Background The contemporary business environment heavily relies on digital commercial strategies to reach broader geographical audiences. Specific Background Micro, small, and medium enterprises currently utilize social platforms like TikTok, Instagram, and Facebook, alongside e-commerce live broadcasting, to market their brands. Knowledge Gap Despite adopting various promotional methods, enterprises often face challenges in task delegation and providing clear content concepts, which leads to off-target audience reach. Aims This study analyzes the digital commercial strategies, specifically social platform content, advertising, and live broadcasting, executed by PT Marsudi Utomo Sejahtera for its Sambel Pak D and herbal medicine brands. Results The qualitative descriptive analysis reveals that combining daily live broadcasting on Shopee and TikTok with targeted advertising and twin-date promotional events significantly scales brand visibility and consumer transactions. Furthermore, dividing labor into specific content, design, buzzer, and advertising teams facilitates organized media production, although misaligned intern task distribution occasionally hinders optimal project execution. Novelty This research provides a direct evaluation of multi-platform commercial integration involving structured team divisions and live commerce within a local food and herbal enterprise. Implications The findings suggest that enterprises must prioritize clear conceptual briefings and targeted media creation over arbitrary posting to maximize audience engagement and return on ad spend. Highlights: Integrating live streaming platforms scales brand visibility alongside consumer transactions. Structured division involving advertising, design, and buzzer teams streamlines promotional e-commerce campaigns. Clear conceptual briefings prevent off-target audience reach while minimizing unoptimized commercial expenditure. Keywords: Social Media, Live Streaming, Consumer Transactions, Content Strategy, Brand Visibility